Towards Using Sensors as Data Sources in Teaching: Requirements for School Curricula-Compatible Sensors - Mubashrah Saddiqa; Marite Kirikova; Rikke Magnussen; Birger Larsen; Jens Myrup Pedersen (Complex Systems Informatics and Modeling Quarterly)
The continuous innovation in modern technologies in various sectors of society has transformed everyday life. It becomes imperative for the educational community to equip the future generation with digital skills. In this article, using qualitative and quantitative research techniques, we define criteria for school curricula-compatible sensors (particularly, for secondary school students in grades 5 through 9). We also develop requirements models for sensor classes that satisfy the school curricula compatibility criteria using requirements engineering techniques. The results show that integrating sensors into schools can improve students’ digital and data skills. Additionally, requirements models can help in developing school curricula-compatible sensors or transforming existing sensors into curricula-compatible sensors.